Kualitas Hidup Pasien Pasca Operasi di RSI Siti Rahmah Padang - Dita Hasni; Kurnia Fajar; Khomeini Khomeini; Budi Yulhasfi Febrianto (FORUM ILMIAH KESEHATAN, 2022)
The World Health Organization (WHO) states that there is an increase in the number of operations, of course this will affect the quality of life of patients. This study aims to determine the quality of life of postoperative patients at RSI Siti Rahmah Padang in 2019. This descriptive study involved 40 patients who visited the Surgery and Pediatric Clinic of RSI Siti Rahmah. This study was limited to variables of gender, age, quality of life, diagnosis and length of patient care. Data were collected through interviews and medical records. Quality of life assessment using a 36-Item Short Form Survey (SF-36) questionnaire. As many as 60% of the patients were women, the mean age was 49.60, there were 35% of patients diagnosed with colonic Ca, the median length of treatment for patients was 3 days, and 82.5% of patients had a quality of life in the good category. It was further concluded that the majority of patients had a good postoperative quality of life.Keywords: quality of life; postoperatively; 6-item short form survey (SF36)ABSTRAK World Health Organization (WHO) menyatakan bahwa terdapat peningkatan jumlah tindakan operasi, tentu saja hal ini akan mempengaruhi kualitas hidup pasien. Penelitian ini bertujuan untuk mengetahui kualitas hidup pasien pasca operasi di RSI Siti Rahmah Padang pada tahun 2019. Penelitian deskriptif ini melibatkan 40 pasien yang berkunjung di Poliklinik Bedah dan Anak RSI Siti Rahmah. Penelitian ini dibatasi pada variabel jenis kelamin, usia, kualitas hidup, diagnosis dan lama perawatan pasien. Data dikumpulkan melalui wawancara dan rekam medik. Penilaian kualitas hidup menggunakan kuisioner 36-Item Short Form Survey (SF-36). Sebanyak 60% pasien adalah perempuan, rerata usia adalah 49,60, ada 35% pasien terdiagnosis Ca colon, median lama perawatan pasien adalah 3 hari, dan 82,5% pasien memiliki kualitas hidup dalam kategori baik. Selanjutnya disimpulkan bahwa mayoritas pasien memiliki kualitas hidup yang baik pasca operasi.Kata kunci: kualitas hidup; pasca operasi; 6-item short form survey (SF36)